Praktik Pemanfaatan Teknologi Virtual Reality Berbasis Mobile untuk Media Pembelajaran Merakit Personal Komputer - Estu Sinduningrum; Atiqah Meutia Hilda; Mia Kamayani (Universitas Mathla'ul Anwar Banten, 2021)
PRACTICES TO USE MOBILE-BASED VIRTUAL REALITY TECHNOLOGY FOR LEARNING MEDIA ASSEMBLING PERSONAL COMPUTER. The Vocational High Schools are still teaching assembling computers in the conventional way. However, this method is deemed ineffective and inefficient, because of the continuous development of computer technology and very expensive prices. The current covid pandemic condition is also a new problem that makes it difficult for students to practice assembling computers face-to-face. This Community Service (PKM) activity aims to utilize virtual reality (VR) technology as a learning medium to simulate PC assembly. The first the PC assembly learning application was made using Java Android program which was adjusted to the basic curriculum for computer assembly. Second, if this application has been successfully created, training will be carried out for students. The training will be carried out in several stages, the first stage by registering, filling out a questionnaire via Google Form. The second stage, the provision of material that will begin with an explanation of the introduction of VR technology. The third stage, is the setting and installation of the PC assembly learning program with VR on the Android cellphone of each participant, followed by the participants practicing the use of the VR program with VR glasses 3 D. The results of the student questionnaire stated that they had previously known that VR technology could be used. as a medium of learning in schools worth 34%. The results of the questionnaire after PKM were held, the results of 88.25% of students felt that VR was useful if it was used in the education sector such as computer assembly.